Investigation of Brash Ice (Overview) - K. E. Sazonov (Лëд и снег)
The urgency of brash ice study is growing in connection with intensive shipping in fast ice zone of freezing seas as well as inland waterways. In addition, an important incentive for such studies is the design and construction of port infrastructure in these water areas. The review shows that the main directions of research refer to three main topics. 1) Investigation of morphometrical brash ice characteristics in navigable channels and harbors, their variability under ambient factors. The most well-studied morphometrical parameters of brash ice are relative channel thickness and its distribution over channel width. Size distribution details about brash ice floes are of great interest for researchers. 2) Investigation of porosity and mechanical properties of brash ice as a granular material taking account of freezing between individual ice blocks. In many respects, these parameters determine the pattern of brash ice interaction with ships and the possibility of their movement. 3) Description of consolidated layer formation in brash ice and refinement of predictions for brash ice growth in the water area under consideration depending on the intensity of ship traffic and the number of degree-days with negative temperatures over the time interval between ship passages. Large attention is given to new methods of studies including full-scale and laboratory experiments, as well as the use of ice basins for this purpose, with a brief review of thermal methods for brash ice management. The paper formulates some of the problems yet to solved, which require extra studies.